Marktintegration ohne Gemeinsame Agrarpolitik: Auswirkungen einer Einbeziehung von Agrarprodukten in die Zollunion mit der EU auf den tur̈kischen Agrarsektor - Harald Grethe (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2004)
– Turkey entered a customs union (CU) with the EU in January 1996. Agricultural trade is not covered by this CU but it is subject to extensive preferential trade rules. In this article, the effects of an inclusion of agricultural products in the CU as well as alternative policy options on the Turkish agricultural sector are analysed. To this aim, a comparative-static, partial equilibrium model of the Turkish agricultural sector is developed. The complete liberalization of the agricultural sector is found to lead to significant comparative static welfare gains of about Euro 670 million as compared to the the status quo. It appears that for most products, with few but significant exceptions, the inclusion of agriculture in the CU with the EU is very similar to the complete liberalization of agricultural trade.
Keywords: 330; Agrarprodukt; Zollunion; Agrarmarkt; Marktintegration; EU-Agrarpolitik; EU-Staaten; Türkei